2021
DOI: 10.1039/d1cc01793d
|View full text |Cite
|
Sign up to set email alerts
|

Arylpentazoles with surprisingly high kinetic stability

Abstract: A co-stabilization method was proposed to design a series of novel arylpentazoles with very high N2-leaving barriers, one of which reached hitherto the highest value of 40.83 kcal mol−1 at the CBS-QB3 level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It has been suggested that an ideal HEDM would have a free-energy activation barrier of ∼30 kcal mol –1 with a half-life of ∼35 years at room temperature . Recently, it has been proposed via CBS–QB3 calculations that it is possible to achieve this level of kinetic stability for arylpentazole by substituting Lewis acids at the ortho positions of the aryl ring . While this has yet to be accomplished experimentally and the size of the molecules makes them cost prohibitive to study with high-level ab inito methods, it would significantly increase the utility of pentazole derivatives by making them safer and easier to work with and store.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that an ideal HEDM would have a free-energy activation barrier of ∼30 kcal mol –1 with a half-life of ∼35 years at room temperature . Recently, it has been proposed via CBS–QB3 calculations that it is possible to achieve this level of kinetic stability for arylpentazole by substituting Lewis acids at the ortho positions of the aryl ring . While this has yet to be accomplished experimentally and the size of the molecules makes them cost prohibitive to study with high-level ab inito methods, it would significantly increase the utility of pentazole derivatives by making them safer and easier to work with and store.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, it has been proposed via CBS−QB3 calculations that it is possible to achieve this level of kinetic stability for arylpentazole by substituting Lewis acids at the ortho positions of the aryl ring. 39 While this has yet to be accomplished experimentally and the size of the molecules makes them cost prohibitive to study with high-level ab inito methods, it would significantly increase the utility of pentazole derivatives by making them safer and easier to work with and store. However, this would be difficult to achieve for the parent pentazole or one of its simpler derivatives without external influences, though it is possible that a pentazole compound could become moderately stable at a lower temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…costabilization method and host-guest strategy). [60][61][62] Single-crystal X-ray diffraction studies showed that cyclo-N 5…”
mentioning
confidence: 99%
“…Notably, the NPA charge in free and LA-stabilized 01 remains positive, in sharp contrast to all of the reported pentazoles (i.e., cyclo-RN 5 with R being a non-F substituent) with a negatively charged N 5 ring. We are aware that the gas phase ring-destruction barriers of a series of arylpentazoles (cyclo-ArN 5 ) were reported very recently to lie in the range of 17.71−20.89 kcal/mol at the CBS-QB3 level, 58 and most of these cyclo-ArN 5 species have been synthesized (though need to be stored at low temperatures 63 ). Thus, we anticipated that both free and LAattached 01 with barriers of 13−23 kcal/mol and large BDEs (see Table S4.4) could have a great likelihood of being synthesized in the laboratory, either spectroscopically or even in the condensed phase.…”
mentioning
confidence: 99%
“…Thus, cyclo -FN 5 is charge anomalous compared to nearly all pentazoles! Unfortunately, a number of theoretical studies have shown a reverse correlation between the ring-destruction stability of cyclo- RN 5 and the electronegativity of R, i.e., the larger electronegativity of R, the lower kinetic stability of cyclo- RN 5 . Understandably, the F atom, the most electronegative element in the periodic table, should make cyclo -FN 5 bear the lowest ring-destruction barrier [6.70 kcal/mol at the CCSD­(T)/aug-cc-pVDZ//MP2­(full)/6-311G­(d) level] . This is surely quite upset, because a low barrier is generally associated with a short lifetime.…”
mentioning
confidence: 99%